STUDENTS PERCEPTION TOWARDS INFORMATION RETRIEVAL VIA SMARTPHONE : A STUDY OF UNIVERSITY OF JAMMU (LIS TODAY, 2024)
The main aim of this research paper is to examine and analyze the perception of user  towards the use of smartphone’s in retrieving information with special reference to the  University of Jammu. Smartphones are bringing the web to our door steps thus enabling the  retrieval of required information from anywhere at any time. The study included total 145  participants. Google forms were distributed online to gather the viewpoint of the participants.  The data was analyzed via MS-Excel. The study revealed that majority of the participants  were females i.e. 73.1% and rest were male i.e. 26.9%. Further, the study revealed that  majority of the participants i.e. 136 owned android phones in comparison to the others. Also,  according to the results majority of the students use the smartphones with the purpose of  retrieving information/ knowledge. In comparison to the use of smartphone with traditional  documents majority of the participants claimed that although being more expensive, yet it is  more informative and time-saving. Despite of these advantages majority of the participants  i.e. 73.1% students claimed that smartphones cannot replace libraries.
Keywords: Data; Information; information retrieval; University of Jammu; Smart phones; Libraries